Chemotherapy Reverses Anti-PD-1 Resistance in One Patient With Advanced Non-small Lung Cell Cancer - Zhao, Lingdi; Ma, Baozhen; Yang, Yonghao; Li, Tiepeng; Han, Lu; Gao, Quanli (Frontiers in Oncology, 2020)
Background: Programmed cell death protein 1(PD-1) blockade has become a standard second-line treatment option for patients with advanced non-small cell lung cancer (NSCLC) without a driver gene mutation. Previous clinical studies showed that the objective response rate (ORR) of PD-1 blockade as second-line treatment for patients with NSCLC was ~20%, and the median progression-free survival (PFS) was ~4 months, with most patients eventually developing a resistance to PD-1 blockade. Although the ORR to chemotherapy after PD-1 blockade resistance was relatively high, the survival time of patients could not be significantly prolonged. Clinical oncologists are unclear about which treatment regimen should be selected after PD-1 blockade failure. Here, we report about a patient with advanced NSCLC and initial PD-1 blockade resistance who was observed to have a rapid partial response (PR) following one dose of chemotherapy and subsequent PD-1 blockade treatment. Case presentation: A 70-year-old woman with a history of left lower lobe lung surgery in March 2018 (pathological stage T1N2M0, EGFR wild-type) presented to our hospital. After six cycles of adjuvant chemotherapy, multiple nodules in both the lungs developed, and were suspected to be metastatic lesions. After another 2 months, the nodules in both the lungs enlarged. From November 2018 to March 2019, the patient received six cycles of pembrolizumab, and computed tomography (CT) confirmed a progressive disease status. She was then managed with 260 mg/m2 albumin paclitaxel once every 3 weeks. Subsequently, chemotherapy was discontinued after one cycle owing to grade three neuromuscular toxicity. Follow-up CT revealed a stable disease in May 2019. She then received another six cycles of pembrolizumab, which resulted in a PR. Conclusion: Chemotherapy may play a role in reversing PD-1 blockade resistance. If failure of PD-1 blockade occurs at first, re-administration of PD-1 blockade may be implemented if first followed by several cycles of chemotherapy. Because there are few reports on the use of chemotherapy to reverse PD-1 resistance, it is necessary to conduct clinical studies with larger patient cohorts to investigate whether chemotherapy can reverse PD-1 blockade resistance.